Optimizing Social Media Engagement for University Branding: A Content Strategy Framework for Higher Education Institutions - Demirer, Dilek Penpece (European Journal of Social Science Education and Research, 2025)
As the higher education market becomes increasingly competitive, universities leverage social media for brand management. However, the principles of effective content strategy in this unique context remain underdeveloped. This study moves beyond descriptive analysis to develop an empirically grounded, strategic framework for optimizing social media content. It employs a quantitative content analysis of 1,250 social media posts from the official Facebook pages of the top ten higher education institutions in Turkey. The impact of key content strategy variables—including content type, post context, content agility, posting source, and temporal factors—on user engagement (likes, comments, shares) is tested using Multivariate Analysis of Variance (MANOVA). The analysis reveals that all tested elements are significant predictors of engagement. Content type and post context are the strongest drivers, with institution-generated "university news" published on weekdays in the afternoon consistently outperforming other strategies. This paper contributes a practical, data-driven "Dynamic Content Framework" for brand managers to enhance brand visibility and optimize resource allocation.